Modern JavaScript for the Impatient - Horstmann, Cay (Addison-Wesley Professional, 2020)
Exploit the Power of Modern JavaScript and Avoid the Pitfalls JavaScript was originally designed for small-scale programming in web browsers, but modern JavaScript is radically different. Nowadays, JavaScript programmers actively embrace functional, object-oriented, and asynchronous programming, while deprecating error-prone concepts from the past. Modern JavaScript for the Impatient is a complete yet concise guide to JavaScript E6 and beyond. Rather than first requiring you to learn and transition from older versions, it helps you quickly get productive with today's far more powerful versions and rapidly move from languages such as Java, C#, C, or C++. Bestselling programming author Cay S. Horstmann covers all you need to know, provided in small chunks organized for quick access and easy understanding. Horstmann's practical insights and sample code help you take advantage of all that's new, avoid common pitfalls and obsolete features, and make the most of modern JavaScript's robust toolchains and frameworks. Quickly master modern JavaScript's implementation of fundamental programming constructs Avoid legacy techniques that create unnecessary complexity and risk Make the most of functional, object-oriented, and asynchronous techniques Use modules to efficiently organize and run complex programs Write more powerful, flexible, and concise programs with metaprogramming Extend JavaScript's power via JavaScript libraries, frameworks, and platforms Whether you're just getting started with JavaScript or you're an experienced developer, this guide will help you write tomorrow's most robust, efficient, and secure JavaScript code. Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details.